2008
DOI: 10.1162/jocn.2008.20060
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Association Cortex in Time Perception

Abstract: The recent upsurge of interest in brain mechanisms of time perception is beginning to converge on some new starting points for investigating this long under studied aspect of our experience. In four experiments, we asked whether disruption of normal activity in human MT/V5 would interfere with temporal discrimination. Although clearly associated with both spatial and motion processing, MT/V5 has not yet been implicated in temporal processes. Following predictions from brain imaging studies that have shown the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 36 publications
15
127
1
5
Order By: Relevance
“…The role of sensory areas in temporal processing is a very recent finding (Bueti et al, 2008b) and indeed is the subject of some debate (Walsh, 2003;Ivry and Schlerf, 2008). Transient disruption of V5/MT can affect temporal discrimination of visual durations (Bueti et al, 2008a), providing some converging evidence for a role of visual cortex in temporal processing. The present findings now demonstrate the existence of a temporal signal much earlier in the visual pathway and in the primary visual cortex and show that this modulation here is retinotopic specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of sensory areas in temporal processing is a very recent finding (Bueti et al, 2008b) and indeed is the subject of some debate (Walsh, 2003;Ivry and Schlerf, 2008). Transient disruption of V5/MT can affect temporal discrimination of visual durations (Bueti et al, 2008a), providing some converging evidence for a role of visual cortex in temporal processing. The present findings now demonstrate the existence of a temporal signal much earlier in the visual pathway and in the primary visual cortex and show that this modulation here is retinotopic specific.…”
Section: Discussionmentioning
confidence: 99%
“…Rather less attention has been paid to structures earlier in the visual pathway (Bueti et al, 2008a). It has been suggested, on theoretical grounds, that primary and extrastriate visual cortex may play a key role in encoding temporal variables.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, rTMS studies have shown that the right posterior parietal cortex has a critical role for timing intervals ( 1 sec) marked by either auditory or visual signals (Bueti, Bahrami, & Walsh, 2008), and for timing longer intervals (Koch, Oliveri, Torriero, & Caltagirone, 2003). In addition, using f MRI has revealed that the parietal cortex, which acts as an interface between sensory and motor processes, is involved in translating temporal information into action .…”
Section: Cerebellummentioning
confidence: 99%
“…Over the past decade, a number of different brain areas have been implicated as key parts of a neural time-keeping mechanism, notably (among many others), event timing in the cerebellum [22], generalized magnitude processing for time, space and number in the right posterior parietal cortex [23,24], working memory related integration in the right prefrontal cortex [25,26], a right frontoparietal network [27], coincidence detection mechanisms using oscillatory signals in fronto-striatal circuits [28], hippocampal time-cells focused on the relation of time and distance [29], as well as integration of ascending interoceptive (that is, body) signals in the insular cortex [30,31]. The participation of many brain areas in the processing of temporal information attest the key role of time in a broad range of cognitive capacities.…”
Section: Time Perception Mechanisms In the Brainmentioning
confidence: 99%